Profile of Patients Admitted in Maternal Intensive Care Unit at BPKIHS, a Tertiary Hospital in Eastern Nepal - Thakur, A; Basnet, P; Agrawal, A; Uprety, D K (Journal of Nepal Health Research Council, 2015)
Background: Maternal death is a tragic event. It can be reduced by prompt recognition of critical illness in pregnancy and earlier initiation of intensive care. The physiological changes of pregnancy and the presence of a fetus complicates the assessment and management of critically ill obstetric patients. The objective of this study was to analyse the basic contributing factors for maternal intensive care unit admission and the maternal outcome. Methods: This was a prospective study conducted in the department of Obstetrics and Gynaecology at B.P. Koirala Institute of Health Sciences, a tertiary hospital in eastern Nepal, for one year duration from Januaryâ€“December 2012. Data like age, diagnosis at admission, intervention, indication for admission, duration of stay and outcome were analysed. Results:Â One hundred and ninety two patients were admitted in one year. Among them 177 were obstetrics related admission and 15 were non obstetrics. Out of 177 patients, 21(11.8%) were antenatal, 123(69.4%) were postnatal and 33(18.6%) had early pregnancy complications. The mean age in years was 25.67Â±7.169. One hundred and seventy one patients (96.6%) were unbooked and only 6(3.3%) were booked. Among the postnatal patients, 83(67.4%) had delivered at BPKIHS, 24(19.5%) at other health centres and 16 (13%) at home. Antepartum eclampsia was the commonest diagnosis. Out of 192 patients, 148(78.12%) were improved, 24(12.5%) had expired,15(7.8%) went against medical advice and 5(1.6%) were referred. The median duration of MICU stay in days (IQR) was 2(1-4). Conclusions: An intensive care unit often offers the opportunity to improve the patient care. Keywords: intensive care; maternal outcome.